Pengaruh Kepercayaan Dan Ketepatan Waktu Terhadap Keputusan Pembelian Pada Aplikasi Grab: Studi Pada Konsumen Kota Bima - Wawan Setiawan; Muhajirin Muhajirin (International Forum of Researchers and Lecturers, 2023)
This research aims to determine the influence of trust and punctuality on purchasing decisions on the Grab application. This research is of associative type. The population used was all consumers using the Grab application (study of consumers in Bima City) who had purchased products on the Grab application. The sampling technique used was purposive sampling so that a sample of 96 respondents was obtained. The research instrument used is a Likert scale questionnaire with data analysis techniques, namely validity test, reliability test, multiple regression analysis, correlation coefficient, determination test, T test and F test. The results of this research conclude that Trust (X1) has a significant effect on Purchasing Decisions (Y), Timeliness (X2) has a significant effect on Purchasing Decisions (Y).